2023
DOI: 10.1101/2023.03.03.23286485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multidimensional analysis reveals distinct immune phenotypes and the composition of immune aggregates in pediatric acute myeloid leukemia

Abstract: Pediatric cancers are characterized by a relatively low mutational burden and therefore, children are thought to be poor candidates for T cell-engaging immunotherapies. Here, we performed a multidimensional characterization of the tumor immune microenvironment in newly diagnosed children with acute myeloid leukemia (AML) and non-leukemic controls. We identified a subset of pediatric AML patients with remarkably high levels of T cell infiltration and a relatively low abundance of anti-inflammatory macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…[95][96][97][98][99][100][101][102] Multiple recent studies of the spatial relationships of immune cells in cancer have pointed toward stemlike CD8+ T cells expressing PD-1 and TCF-1/TCF-7 as a hub for anti-tumor immunity, often in complex with T helper and myeloid cell populations, such as dendritic cells. 90,92,[103][104][105][106] For myeloid malignancies, however, such immune networks have been only minimally evaluated (for example, in the pediatric AML setting 107 ) in part due to the technical obstacles of applying high dimensional sequencing and spatial profiling approaches to marrow tissue that has been conventionally processed using harsh decalcification procedures, though advancing technologies and analytical methods may overcome this challenge. [108][109][110] The response of AML to immunotherapies such as ICB have been disappointing, 65,111 and defining the role of TLS-like structures or other cellular networks could serve to advance our understanding of the critical cellular players needed to coordinate an effective anti-leukemia response.…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97][98][99][100][101][102] Multiple recent studies of the spatial relationships of immune cells in cancer have pointed toward stemlike CD8+ T cells expressing PD-1 and TCF-1/TCF-7 as a hub for anti-tumor immunity, often in complex with T helper and myeloid cell populations, such as dendritic cells. 90,92,[103][104][105][106] For myeloid malignancies, however, such immune networks have been only minimally evaluated (for example, in the pediatric AML setting 107 ) in part due to the technical obstacles of applying high dimensional sequencing and spatial profiling approaches to marrow tissue that has been conventionally processed using harsh decalcification procedures, though advancing technologies and analytical methods may overcome this challenge. [108][109][110] The response of AML to immunotherapies such as ICB have been disappointing, 65,111 and defining the role of TLS-like structures or other cellular networks could serve to advance our understanding of the critical cellular players needed to coordinate an effective anti-leukemia response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in AML, BCP-ALL, and various other cancers has shown that the efficacy of bispecific T cell-engagers and adoptive cell therapy largely depends on the presence and function of various immune cell populations in the tumor microenvironment. 8,[42][43][44][45][46][47][48] To understand whether pediatric CD19 + t(8;21) AML patients may represent a subgroup with potential to respond to CD19-directed immunotherapies, we characterized their tumor immune microenvironment using immunogenomic computational approaches applied to diagnostic BM bulk RNA-seq data (Figure 5A). Towards this end, we deconvoluted the immune cell abundance in the BM of treatment-naïve CD19 + t(8;21) AML (n=5), CD19t(8;21) AML (n=5), other AML genotypes (n=30), and nonleukemic controls (n=4) using CIBERSORTx and the TIDE algorithm.…”
Section: The Composition Of the Bone Marrow Immune Microenvironment O...mentioning
confidence: 99%
“…Furthermore, single-cell RNA-sequencing of end-of-induction BM in pediatric AML revealed a predominance of M1-like macrophages in patients that remained in complete remission after standard chemotherapy, while enrichment of M2-like macrophages was identified in patients that relapsed [ 41 ]. In addition, we previously identified that a predominance of M2-like macrophages was associated with non-response to the bispecific T cell-engager flotetuzumab [ 13 ]. Thus, it appears that M2-like macrophages play an important role in supporting leukemogenesis and therapy resistance, while M1-like macrophages may have anti-tumoral properties in AML.…”
Section: The Innate Immune System In the Tumor Microenvironment Of Amlmentioning
confidence: 99%
“…For AML, the alleged TME is the bone marrow (BM) and includes, next to tumor cells, immune and other normal hematopoietic, stromal, and endothelial cells [12]. Studies in both adult and pediatric AML patients have shown that the BM of a subgroup of patients is immune-depleted (or "cold"), which has been associated with reduced responses to T cell-based immunotherapies in both AML and solid cancers [13][14][15][16][17]. To date, most studies that investigated the TME of AML focused on T cells, while less attention has been paid to the innate immune compartment [11,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation